Models of Birdsong (Physics) - Trevisan, Marcos Alberto (2009)
The avian vocal organ (the syrinx) is a versatile organ located at the junction of the primary bronchi and the trachea, where free moveable connective tissue membranes, the labia, are set in oscillatory motion through an energy exchange from the airstream propelled from the air sacs. The rapid membrane oscillations generate air pressure perturbations, sound waves that travel through the trachea and beak before leaving the bird under the form of complex songs. At the base of the song organization stand the syllables, stereotyped acoustic elements arranged into motifs that can be in turn recombined to form the songs, ultimately revealing the action of a sophisticated neural vocal program. The syrinx is therefore a key element in the articulation between the neural vocal program and the singing behavior. This article deals with the mathematical models of the syrinx, whose nonlinear nature allows to explain the bulk of acoustical properties of the songs, while capable of producing synthetic songs driven by real physiological instructions recorded from the activity of muscles and air sac pressure during spontaneous singing, showing good qualitative agreement with experimental song recordings.